2000
DOI: 10.1074/jbc.m005459200
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic, p160 Coactivator-dependent Enhancement of Estrogen Receptor Function by CARM1 and p300

Abstract: Members of the p160 coactivator family (steroid receptor coactivator-1 (SRC-1), glucocorticoid receptor interacting protein 1 (GRIP1), and activator of thyroid and retinoic acid receptors (ACTR)) mediate transcriptional activation by nuclear receptors. After being recruited to the promoter by nuclear receptors, the p160 coactivator transmits the activating signal via two C-terminal activation domains, AD1 and AD2. AD1 is a binding site for the related coactivators cAMP-response element binding protein binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
172
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(185 citation statements)
references
References 37 publications
12
172
1
Order By: Relevance
“…While less evidence exists for other events occurring during the third step, cell transfection studies have suggested that the arginine methyltransferase CARM1 can synergize with p160 proteins and p300 to enhance ligand-dependent transcriptional activation by NRs, possibly through its ability to methylate histone H3 (Chen et al, 2000). A second study demonstrated that p300 can also interact with the histone H2A/H2B chaperone protein NAP1 (Shikama et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…While less evidence exists for other events occurring during the third step, cell transfection studies have suggested that the arginine methyltransferase CARM1 can synergize with p160 proteins and p300 to enhance ligand-dependent transcriptional activation by NRs, possibly through its ability to methylate histone H3 (Chen et al, 2000). A second study demonstrated that p300 can also interact with the histone H2A/H2B chaperone protein NAP1 (Shikama et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying mechanism for requirement of various chromatin remodeling factors remains obscure. CARM1 cooperates synergistically with the SRC family of coactivators and CBP/p300 to enhance gene activation by NRs as observed in transient transfection assays (Chen et al, 2000). In addition, CARM1 associates with the SWI/SNF complex and this association seems to enhance CARM1's HMT activity.…”
Section: Discussionmentioning
confidence: 79%
“…CARM1 methylates histone H3 at Arg 2, 17 and 26 . CARM1 cooperates synergistically with the SRC family of coactivators and CBP/p300 to enhance transcriptional activation by NRs in transient transfection assays (Chen et al, 2000). In addition, CARM1 associates with the SWI/SNF complex and this association seems to enhance the HMT activity of CARM1 (Xu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The functional synergy between p300 and CARM1 and between PRMT1 and CARM1 as coactivators for nuclear receptors also suggests a possible cooperation between acetylation and methylation of various histones (Chen et al, 2000a;Koh et al, 2001;Lee et al, 2001). Methylation could also in¯uence the e ciency with which other types of covalent histone modi®cations occur, as illustrated already by the negative e ect that methylation of lysine 9 of histone H3 has on phosphorylation of serine 10 and the cooperative e ect on transcriptional activation by acetylation and phosphorylation of lysine 14 and serine 10, respectively, on histone H3 (Cheung et al, 2000a;Lo et al, 2000).…”
Section: Lysine Methylationmentioning
confidence: 99%
“…Methyltransferases CARM1 and PRMT1 bind to a C-terminal activation domain (AD2) of p160 coactivators and can only function as nuclear receptor coactivators when co-expressed with a p160 coactivator with an intact AD2 region (Chen et al, 1999a(Chen et al, , 2000a. The function of p300 as a nuclear receptor coactivator is similarly dependent on co-expression of a p160 coactivator with an intact AD1 region, which is the binding site for p300 (Chen et al, 2000a;Li et al, 2000). These results suggest that both methyltransferases and acetyltransferases are recruited to the promoter through their physical interaction with speci®c domains of p160 coactivators, which are recruited to the promoter by direct interactions with the DNA-bound nuclear receptors.…”
Section: Role Of Protein Methylation In the Coactivator Function Of Pmentioning
confidence: 99%